The Main Progress of Perovskite Solar Cells in 2020–2021 - Wu, Tianhao; Qin, Zhenzhen; Wang, Yanbo; Wu, Yongzhen; Chen, Wei; Zhang, Shufang; Cai, Molang; Dai, Songyuan; Zhang, Jing; Liu, Jian; Zhou, Zhongmin; Liu, Xiao; et al. (Nano-Micro Letters, 2021)
Perovskite solar cells (PSCs) emerging as a promising photovoltaic technology with high efficiency and low manufacturing cost have attracted the attention from all over the world. Both the efficiency and stability of PSCs have increased steadily in recent years, and the research on reducing lead leakage and developing eco-friendly lead-free perovskites pushes forward the commercialization of PSCs step by step. This review summarizes the main progress of PSCs in 2020 and 2021 from the aspects of efficiency, stability, perovskite-based tandem devices, and lead-free PSCs. Moreover, a brief discussion on the development of PSC modules and its challenges toward practical application is provided. Highlights: 1 Recent progress of efficiency and long-term stability for perovskite solar cells, and the development of perovskite-based tandem solar cells are described. 2 The progress of lead-free perovskite solar cells and their potential for industrial production are discussed in detail. 3 The current status, ongoing challenges, and the future outlooks of perovskite solar cells are highlighted.